GLOBALISASI DAN PERPINDAHAN LINTAS BATAS LIMBAH BERBAHAYA - Anaya Noora Pitaningtyas (Jurnal Kriminologi Indonesia, 2010)
This paper is pondering about trafficking of dangerous waste across border. The reason why such act considered to be a harmful act to community health and environment since many industrious and developed countries were willing to pay a lot of money for undeveloped countries to be their dumping ground. This explains why many undeveloped countries tend to receive such dangerous waste. Trafficking of dangerous waste from developed to undeveloped countries exists in two form, cargo and trade. Cargo means that trafficking dangerous waste across border were considered to be illegal. Trade means that it was conducted through a legal mechanism. This paper explains such phenomenon by linking economic and political powers through the used of dependentia and world system theory. In concluding remark, it is recommended that industry from developed countries must produced, recycled and reused material on components it manufactured so it will not harm the environment. And for the undeveloped countries are expected to be consistent with the Basel Convention which banned receiving such dangerous waste.